철강산업 부생가스를 이용한 고순도 수소 제조 공정의 반응 조건 최적화 - 김성중(Sungjoong Kim); 고동준(Dongjun Koh); 최한슬(Hanseul Choi); 김준우(Joonwoo Kim); 김우형(Woohyoung Kim) (한국수소 및 신에너지학회 논문집, 2016)
Low-priced hydrogen is required in petrochemical industry for producing low-sulfur oil, and upgrading low-grade crude oil since environmental regulations have been reinforced. Steel industry can produce hydrogen from by-product gases such as Blast Furnace Gas (BFG), Coke Oven Gas (COG), and Linze Donawitz Gas (LDG) with water gas shift (WGS) reaction by catalysis. In this study, we optimized conditions for WGS reaction with commercial catalysts by BFG and LDG. In particular, the influence on activity of gas-hourly-space-velocity, and $H_2O/CO$ ratios at different temperatures were investigated. As a result, 99.9%, and 97% CO conversion were showed with BFG, and LDG respectively under $350^{°}C$ High Temperature Shift (HTS), $200^{°}C$ Low Temperature Shift (LTS), 3.0 of $H_2O/CO$, and $1500h^{-1}$ of GHSV. Furthermore, 99.9% CO conversion lasted for 250 hours with BFG as feed gas.